Inland empire [videorecording (Blu-Ray)] - Lynch, David, 1946-; Dern, Laura; Irons, Jeremy, 1948-; Theroux, Justin; Stanton, Harry Dean, 1926-2017; Gruszka, Karolina, 1980-; Hencz, Jan; Ladd, Diane; Macy, William H., 1950- (Criterion collection, 2023)
'Strange, what love does.' The role of a lifetime, a Hollywood mystery, a woman in trouble...David Lynch's first digitally shot feature makes visionary use of the medium to weave a vast meditation on the enigmas of time, identity, and cinema itself. Featuring a tour de force performance from Laura Dern as an actor on the edge, this labyrinthine Dream Factory nightmare tumbles down an endless series of unfathomably interconnected rabbit holes as it takes viewers on a hallucinatory odyssey into the deepest realms of the unconscious mind.